Improving Students’ Reading Comprehension in Narrative Text Through Students Team Achievement Division (STAD) - Farizawati Farizawati; Mustakim Sagita; Rengganis Siwi Amumpuni (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of the study was to find out whether the use of the students who are taught English by using the Students Team Achievement Division and those who are taught English by using other methods is increasing reading skills. The writer used Student Team Achievement Division (STAD) to teach the students. The Design of the research was quantitative research. The instrument used Student Team Achievement Division (STAD) to collect data in this research was a set of tests, which consisted of test that are Pre-test and Post-test. A pre-test was given before the writer treated the students by using techniques, in order to find out the student’s ability in mastering reading skills. Post-test was given after the writer did experimental teaching six times. It was aimed to find out the improvement of the student’s ability in mastering speaking after teaching students with used classroom debate techniques. The result of the data analysis revealed that the experimental class had a total score of 832, whereas the control class had a total score of 173,377. The experimental class had a mean score of 20,133, while the control class had a mean score of 16,76. It was discovered that the experimental class's mean difference score was greater than the control class's (20,133-16,76). The outcome was, on the other hand, 0.99. Because of that, higher than (20,33 16,76). It means, was accepted. And the conclusion indicated that the ability of the students in mastering reading had increased after the writer Student Team Achievement Division (STAD) technique.